STUDENTS’ ANXIETY TOWARDS MATHEMATICS - Khairatul Ulya; Nurlaila Fazraini; Dahliana Lubis (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2019)
This article is a liteature review focuses on students’ mathematical anxiety and its influence on students’ daily lives includin fear, anxiety, panic, lack of confidence, uncomfortable situation. Review analysis result showed that there are some physiological components that disturbing students’ anxiety and there are eight solutions to decrease mathematical anxiety, namely providing rational understanding, instilling a sense of self-confidence, eliminating negative assumptions about mathematics, learning is conducted by various methods, prioritizing concepts, making learning fun, inserting mathematics in everyday conversation, and instilling a sense of responsibility in students. Furthermore, mathematical anxiety can be influenced by many factors, one of which is fear of mathematics. As a result, this will certainly disrupt the teaching and learning process and the concentration of students that have an impact on student learning outcomes. Abstrak Artikel ini merupakan review literatur tentang kecemasan matematika pada siswa serta pengaruhnya terhadap kehidupan yang meliputi beberapa gejala, yaitu rasa takut, gelisah, panik, kurang percaya diri, tidak merasa nyaman. Hasil analisis review literature menunjukka bahwa terdapat beberapa komponen penyebab terganggu fisiologis siswa yang mengalami kecemasan serta delapan solusi untuk mengatasi kecemasan matematika yaitu memberikan pemahaman secara rasional, menanamkan rasa kepercayaan diri, menghilangkan anggapan negatif terhadap matematika, pembelajaran dilakukan dengan berbagai macam metode, mengutamakan konsep, jadikan pembelajaran menyenangkan, menyisipkan matematika pada pembicaraan sehari-hari, dan menanamkan rasa tanggung jawab pada siswa siswa itu sendiri. Lebih lanjut kecemasan kecemasan matematika dipengaruhi oleh banyak faktor, salah satunya yaitu ketakutan terhadap pelajaran matematika. Akibatnya, hal tersebut tentu akan mengganggu proses belajar mengajar serta konsentrasi siswa yang berdampak pada hasil belajar siswa. Kata kunci: Kecemasan Siswa, Matematika, Hasil Belajar